Effect of cadmium on the germinative parameters of bread wheat - BOUZIANI, YAMNA; Degaichia, H.; Benmoussa, M. (Revista Mexicana de Ciencias Agrícolas, 2019)
The wheat is being a plant largely cultivated for its seeds and its straw wherefore the research of tolerant varieties to this dangerous element for the plant or the human health is necessary. Its concentrations increase day after day in the ground considering the development of the farming which involves the intensive contributions of this polling metal element. Objectives of this study is to test the effect of a range of cadmium concentration from 0 to 200 mg L-1 Cd+2on the parameters of germination of two varieties of bread wheat Anza and Hiddab. The results show that the phytotoxicity increases, according to the increase in the Cd amount on the rate of germination, root and shoot length, root and shoot dry weight and tolerant index compared with the control for both varieties studied, nevertheless, Hiddab variety shows more sensitivity when compared to Anza variety. The inhibiting effect of cadmium on the germination stage can be continued in the advanced stages of plant cycle and disturb its physiological aspects.
Keywords: Triticum aestivum L.; cadmium; phytotoxicity; tolerance index